2006
DOI: 10.1039/b514859f
|View full text |Cite
|
Sign up to set email alerts
|

Design of targeting ligands in medicinal inorganic chemistry

Abstract: This tutorial review will highlight recent advances in medicinal inorganic chemistry pertaining to the use of multifunctional ligands for enhanced effect. Ligands that adequately bind metal ions and also include specific targeting features are gaining in popularity due to their ability to enhance the efficacy of less complicated metal-based agents. Moving beyond the traditional view of ligands modifying reactivity, stabilizing specific oxidation states, and contributing to substitution inertness, we will discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
203
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(206 citation statements)
references
References 50 publications
1
203
0
2
Order By: Relevance
“…[15] Metal complexes functionalised with carbohydrates but containing other cores for metal complexation are increasingly being studied in medicinal inorganic chemistry; examples include Re and Tc complexes for use as radiotracers. [16] 2,2'-Dipicolylamine, [17] 3-hydroxypyridone [18] and 2-hydroxybenzyl [19] derivatives of different monosaccharides, for example, have been used as chelators for Tc and Re carbonyl cores, and similar complexes have been reported from 1,3-diamines of sugars. [20] Saccharide-functionalised bis(quinolinolyl)amino acids have also been complexed to a rhenium tricarbonyl core, [21] and glucose and 2-deoxyglucose have been functionalised at C-1 with iminodiacetic acid and the resulting ligands complexed with Re and Tc.…”
Section: A C H T U N G T R E N N U N G (Co)mentioning
confidence: 98%
“…[15] Metal complexes functionalised with carbohydrates but containing other cores for metal complexation are increasingly being studied in medicinal inorganic chemistry; examples include Re and Tc complexes for use as radiotracers. [16] 2,2'-Dipicolylamine, [17] 3-hydroxypyridone [18] and 2-hydroxybenzyl [19] derivatives of different monosaccharides, for example, have been used as chelators for Tc and Re carbonyl cores, and similar complexes have been reported from 1,3-diamines of sugars. [20] Saccharide-functionalised bis(quinolinolyl)amino acids have also been complexed to a rhenium tricarbonyl core, [21] and glucose and 2-deoxyglucose have been functionalised at C-1 with iminodiacetic acid and the resulting ligands complexed with Re and Tc.…”
Section: A C H T U N G T R E N N U N G (Co)mentioning
confidence: 98%
“…It was demonstrated that the antibacterial activity was increased upon chelation making the ligand a more powerful agent [5,6]. The complexation of derivatives of sterically hindered o-diphenols and o-aminophenols with Cu(II), Co(II), Ni(II), and Zn(II) ions exhibited antioxidant, antiviral, and antimicrobial activity with low toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, carbohydrate-metal conjugation could be expected to show favorable biological and physiochemical properties including biocompatibility, enhanced water solubility, enantiomeric purity, increased stability of the metal core, and reduced or no toxicity. Most importantly, tumor selectivity can be achieved through the coordinated carbohydrate ligands exploiting upregulated signaling pathways and/or certain glycolytic enzymes within the altered cancer cell metabolism [55].…”
Section: Why Metal-based Glycoconjugates?mentioning
confidence: 99%